Experiences with training groups of nursing home administrators in the Netherlands - Wimmers, M F (Gerontologie, 1980)
A national organization of residential homes for the elderly has sponsored a program of training groups to help improve the functioning of directors of the homes. Staff members from the department of social gerontology of the Catholic University Nijmegen are involved as trainers of the group, in cooperation with the main office of the organization. The motivation for setting up this program is reported, along with some demographic characteristics of the directors and a description of the complicated structure in which the director must function. The training groups are then discussed: the folowing aspects of the groups receive attention: a. the recruitment of participants and intake; b. the participants; c. the trainers; d. the methods used; e. topics and issues discussed; and f. the effects of participation in the group, according to preliminary results of research.